Designed a Waste Management Application by Applying Requirements Engineering Methods to Meet User Needs and Expectations - Lisda, Lisda; Febrianto, Dany Candra; Kusumastuti, Rajnaparamitha (Infotekmesin, 2025)
Efforts to manage waste through recycling have been implemented frequently but continue to receive minimal attention from the public, who are daily contributors to waste generation. As a result, the volume of waste keeps increasing, leading to environmental pollution, such as ecosystem damage, unpleasant odors, and blockages in waterways. This research aims to demonstrate that waste management can be enhanced by integrating data to uncover insights that can inform new strategies for addressing excess waste. In this study, a prototype for a waste recycling application was developed, focusing on digital-based waste management using IoT technology. The system incorporates sensors capable of measuring waste volume as a supporting tool developed using the requirements engineering method. Questionnaires were distributed to 30 respondents to gather feedback on platform designs and IoT product designs. Through requirements validation testing, the results showed that 70% of the 30 respondents approved the platform design, while 63.2% approved the IoT product design.